Measurement of the effective B s 0→K +K - lifetime - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2012)
A precise determination of the effective B s 0→K +K - lifetime can be used to constrain contributions from physics beyond the Standard Model in the Bs0 meson system. Conventional approaches select B meson decay products that are significantly displaced from the B meson production vertex. As a consequence, B mesons with low decay times are suppressed, introducing a bias to the decay time spectrum which must be corrected. This analysis uses a technique that explicitly avoids a lifetime bias by using a neural network based trigger and event selection. Using 1.0 fb -1 of data recorded by the LHCb experiment, the effective B s 0→K +K - lifetime is measured as 1.455±0.046(stat.)±0.006(syst.)ps. © 2012 CERN.